The job guarantee: Design, jobs, and implementation - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2018)
The job guarantee (JG) is a public option for jobs. It is a permanent, federally funded, and locally administered program that supplies voluntary employment opportunities on demand for all who are ready and willing to work at a living wage. While it is first and foremost a jobs program, it has the potential to be transformative by advancing the public purpose and improving working conditions, people's everyday lives, and the economy as a whole. This working paper provides a blueprint for operationalizing the proposal. It addresses frequently asked questions and common concerns. It begins by outlining some of the core propositions in the existing literature that have motivated the JG proposal. These propositions suggest specific design and implementation features. (Some questions are answered in greater detail in appendix III). The paper presents the core objectives and expected benefits of the program, and suggests an institutional structure, funding mechanism, and project design and administration.
Keywords: D6; E2; E6; H1; H3; H4; H5; J2; J3; J4; 330; Job Guarantee; Unemployment; Full Employment; Living Wage; Policy Design